Arbutin reduces cognitive deficit and oxidative stress in animal model of Alzheimer's disease. (2nd November 2019) - Dastan, Zohreh; Pouramir, Mahdi; Ghasemi-Kasman, Maryam; Ghasemzadeh, Zahra; Dadgar, Masoumeh; Gol, Mohammad; Ashrafpour, Manouchehr; Pourghasem, Mohsen; Moghadamnia, Ali Akbar; Khafri, Soraya
Abstract: Objectives: Recent evidences have shown the beneficial effects of natural products for treating of Alzheimer's disease (AD). Arbutin is derived from Pyrus biossieriana and exerts a wide range of pharmacological activities including anti-inflammatory and anti-oxidant effects. The present study was designed to examine the protective effects of arbutin on streptozotocin (STZ)-induced neurotoxicity in rats. Materials and methods: The spatial memory impairment was induced by intracerebroventricular (i.c.v) microinjection of STZ (3 mg/kg, 10 μL). Animals received the pretreatment of arbutin (50 mg/kg) for 21 days before STZ injection. The Morris Water maze (MWM) task was used to study the spatial learning and memory. The levels of oxidative stress markers including malondialdehyde (MDA), nitrite and carbonyl were measured in serum and hippocampus samples. In addition, antioxidant level was assessed by ferric reducing antioxidant power (FRAP) test. Results: The obtained result indicated that administration of STZ is led to memory impairment and increases the levels of oxidative stress markers in the hippocampus tissues. Conversely, arbutin improves spatial memory and reduces oxidative and nitrosative stress, as evidenced by a significant decrease in the amount of MDA and nitrite in the serum and hippocampus. In addition, an increase in FRAP levels of hippocampus was observed in arbutin receiving animals. The protein carbonyl content was not reduced in arbutin receiving animals. Conclusion: It could be concluded that arbutin protects the brain against STZ-induced memory impairment and oxidative damage in the hippocampus. The neuroprotective effect of arbutin might be mediated through its antioxidant and free radical scavenging effects.